Bulbophyllum section Rhytionanthos (Orchidaceae) in Vietnam with description of new taxa and new national record - Dang, Minh Quan; Averyanov, Leonid V.; Dang, van Son; Maisak, Tatiana; Bui, van Huong; Tu, Bao Ngan; Truong, Ba Vuong (Phytotaxa, 2022)
The paper presents a taxonomic review of Bulbophyllum section Rhytionanthos for the flora of Vietnam and provides the key for its species’ identification. A new species, B. truongtamii and a new variety, B. taeniophyllum var. denticulatoalatum are described for science. Bulbophyllum nodosum is reported for the first time from the country. Bulbophyllum strigosum, described 20 years ago based on cultivated plant of uncertain origin was rediscovered in NE Vietnam. For this species, location and detailed description are reported. Analytical photos, data on phenology, ecology, and distribution are presented for all studied species. The morphological comparison table of the new species, new variety and newly recorded species segregating them from similar species are presented.